FINANCIAL SYSTEM IN ISLAM - Ifham Choli (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2021)
Islamic finance is a system that originates from the Al-Quran and Sunnah, as well as from the interpretations of the scholars of these sources of revelation. The economic system is something that is important to the economy of a country. The economic system is formed due to various complex factors, such as ideology and belief system, way of life, geographical environment, politics, socio-culture, etc. The structure of Islamic finance has emerged as one of the most important modern implementations of the Islamic legal system and successful, and as a test for the renewal and development of Islamic law in the future. This research uses descriptive qualitative method. This study aims to ensure that the financial system is carried out in accordance with Islamic teachings. The instruments of the Islamic financial system are zakat, prohibition of usury, economic cooperation, social security, prohibition against dirty business practices and the role of the state in the economic system. Keuangan Islam adalah sebuah sistem yang bersumber dari Al-Quran dan Sunnah, serta dari penafsiran para ulama terhadap sumber-sumber wahyu tersebut. Sistem ekonomi merupakan sesuatu yang penting bagi perekonomian suatu negara. Sistem ekonomi terbentuk karena berbagai faktor yang kompleks, misalnya ideologi dan sistem kepercayaan, pandangan hidup, lingkungan geografi, politik, sosial budaya, dan lain-lain.. Struktur keuangan Islam telah tampil sebagai salah satu implementasi modern dari sistem hukum Islam yang paling penting dan berhasil, dan sebagai ujicoba bagi pembaruan dan perkembangan hukum Islam pada masa mendatang. Penelitian ini menggunakan metode kualitatif deskriptif. Penelitian ini bertujuan agar sistem keuangan dilakukan sesuai ajaran Islam. Instrument sistem keuangan Islam adalah zakat, larangan riba, kerjasama ekonomi, jaminan sosial, Pelarangan terhadap praktek-praktek usaha yang kotor serta adanya peranan negara dalam sistem ekonomi.